Grazing-incidence neutron-induced fluorescence probes density profiles of labeled molecules at solid/liquid interfaces - Schneck, Emanuel; Jentschel, Michael; Gege, Christian; Tanaka, Motomu; Demé, Bruno (Langmuir, 2013)
We report on the use of characteristic prompt γ-fluorescence after neutron capture induced by an evanescent neutron wave to probe densities and depth profiles of labeled molecules at solid/liquid interfaces. In contrast to classical scattering techniques and X-ray fluorescence, this method of “grazing-incidence neutron-induced fluorescence” combines direct chemical specificity, provided by the label, with sensitivity to the interface, inherent to the evanescent wave. We demonstrate that the formation of a supported lipid membrane can be quantitatively monitored from the characteristic fluorescence of 157Gd3+ ions bound to the headgroup of chelator lipids. Moreover, we were able to localize the 157Gd3+ ions along the surface normal with nanometer precision. This first proof of principle with a well-defined model system suggests that the method has a great potential for biology and soft matter studies where spatial resolution and chemical sensitivity are required.
Gesehen am 12.07.2021